Towards an integrated approach to health and medicine in Africa - Kezia Batisai (Taylor & Francis Group, 2016)
This article frames the intersections of medicine and humanities as intrinsic to understanding the practice of health care in Africa. Central to this manuscript, which draws on empirical findings on the interplay between HIV and AIDS and alternative medicine in Zimbabwe is the realisation that very limited research has been undertaken to examine 'HIV/AIDS patient behaviour' with respect to choice of therapy on the continent [Bene, M. & Darkoh, M. B. K. (2014). The Constraints of Antiretroviral Uptake in Rural Areas: The Case of Thamaga and Surrounding Villages, Botswana. SAHARA-J: Journal of Social Aspects of HIV/AIDS, 11(1), 167-177. doi:10.1080/17290376.2014.972057; Chavunduka, G. (1998). Professionalisation of Traditional Medicine in Zimbabwe, Harare, Jongwe Printers; O'Brien, S. & Broom, A. (2014). HIV in (and out of) the Clinic: Biomedicine, Traditional Medicine and Spiritual Healing in Harare. SAHARA-J: Journal of Social Aspects of HIV/AIDS, 11(1), 94-104. doi:10.1080/17290376.2014.938102]. As such, a social approach to health-seeking behaviour questions how decisions about alternative therapies including herbal remedies, traditional healing and faith healing are made. The paper unpacks the realities around how people living with HIV and AIDS - who span different age groups and profess various religious backgrounds, faced with an insurmountable health challenge against a background of limited resources and no cure for the virus - often experience shifts in health-seeking behaviour. Grappling with seemingly simple questions about 'when, where and how to seek medical attention', the paper provides pointers to therapy choices and health-seeking behaviour; and it serves as a route into deeper and intense healthcare practice explorations. In conclusion, the paper proposes that medicine and the humanities should engage seriously with those social aspects of HIV and AIDS which call for an integrated approach to healthcare practice in Africa. If combined, medicine and the humanities might achieve what neither would alone.